Cervical length by ultrasound as a predictor of preterm labour - Begum, Jasmina; Behera, Ashok Kumar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Objective of current study was to evaluate cervical length by transabdominal and transvaginal ultrasonography at 14-24 weeks of gestation in asymptomatic women for predicting women at risk of preterm delivery and to find out the one method which is more accurate of the two. Methods: Fifty one women were enrolled in this prospective study. Women with cervical incompetence, multiple gestation, maternal medical diseases, previous cervical surgery were excluded. Each woman underwent a transabdominal and transvaginal ultrasonographic cervical length measurement. The period of gestation at delivery in these women was then correlated with sonographic findings. Statistical comparisons were made between the two ultrasonographic methods. Results: Preterm delivery occurred in 37.2% of the women. By transabdominal sonography it was seen that with cervical length of less than 3cm at 14-24 weeks, majority (63.15%) delivered preterm. The mean cervical length of cases who delivered preterm was 3.3 ± 0.9 cm. Whereas the mean cervical length of cases that had term delivery was 3.5 ± 0.6, and majority (86.2%) had cervical length of more than 3 cm, similar trend was also seen with transvaginal sonography, majority (78.9%) of cases with cervical length of less than 3 cm delivered preterm. The mean cervical length of cases who delivered at term was 3.1 ± 0.4 and the mean cervical length of cases who delivered preterm was 2.85 ± 0.5 cm. There was definitive positive correlation between cervical length at 14-24 weeks and period of gestation at delivery. On analysis, prediction of risk of preterm delivery by cervical length cut off value on the basis of the median at earlier weeks, 35 mm for transabdominal and 30 mm for transvaginal sonography, it was observed that transabdominal sonography with a sensitivity of 63.15% and specificity of 71.8%, predicted relative risk of 2.47 which was not significant (P <0.1) but transvaginal sonography with sensitivity of 78.9% and specificity of 81.2 predicted relative risk of 5.35 which was significant (P <0.001). Conclusions: Transvaginal ultrasonography seems to be the optimal method for assessment of cervical length in the second trimester and for screening for spontaneous preterm delivery.